PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA DAN TEKA TEKI SILANG (TTS) TERHADAP HASIL BELAJAR SISWA KELAS XI-4 SMA NEGERI 3 SALATIGA - Nahar, Kamelia; Nikmah, Anna Royyana; Kriswandani, Kriswandani (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to determine the effect of using the Problem Based Learning (PBL) model assisted by GeoGebra and Crossword Puzzles on the learning outcomes of 11th-grade students (class XI-4) at SMA Negeri 3 Salatiga. The research method used is experimental research with 26 students from class XI-4 at SMA Negeri 3 Salatiga during the 2024/2025 academic year as the subjects. The design used in this study is the One-Group Pretest-Posttest design. The data collection techniques in this study include tests and observations. The data analysis technique used in this study is the Wilcoxon test. The results of the study indicate that the application of the Problem Based Learning (PBL) model assisted by GeoGebra and Crossword Puzzles has a significant effect on the learning outcomes of 11th-grade students (class XI-4) at SMA Negeri 3 Salatiga. This is evident from the Wilcoxon test results with a significance value of 0.017 < 0.05, which shows that there is a difference in the average pretest and posttest results, where the average score after being taught using the Problem Based Learning model assisted by GeoGebra and Crossword Puzzles is 70.96, while the average score before the application of the model was 57.88. This means that the average score after being taught using the Problem Based Learning model assisted by GeoGebra and Crossword Puzzles is better or has a positive effect compared to the average score before the model was applied. Additionally, the use of the Problem Based Learning model assisted by GeoGebra and Crossword Puzzles is also able to increase students' activity, motivation, conceptual understanding, and interest in mathematics learning, while creating interactive learning with technology integration.